Impact of Non-Agricultural Labor Transfer on the Ecological Efficiency of Cultivated Land: Evidence from China - Weijuan Li; Jinyong Guo; Tian Xie (Agriculture)
The ecological efficiency of cultivated land utilization is closely related to food security and the sustainable development of agriculture. As an important actor in the utilization of cultivated land, the transfer of labor to non-agricultural sectors and its impact on ecological efficiency remain underexplored. Taking China as an example, this study employs push–pull theory, technology factor substitution theory, and land scale economy theory to explore the motivations and mechanisms of non-agricultural labor transfer. An empirical analysis was conducted using provincial panel data from 2011 to 2023. The research methods include the super-efficiency SBM model, fixed effect model, mediating effect model, and threshold effect model. The results are as follows: (1) Non-agricultural labor transfer promotes improvements in the ecological efficiency of cultivated land utilization. A 1% growth in non-agricultural labor transfer is associated with a 0.615% improvement in the ecological efficiency of cultivated land utilization. The impact is especially evident in the main grain-producing areas and northern regions. (2) As a modern agricultural production factor, agricultural machinery plays a mediating role in factor substitution at the farmland stage, accounting for 39% of the effect. (3) The scale of agricultural land operation exhibits a single threshold effect with a threshold value of 1.1577. Against the backdrop of widespread non-agricultural labor transfer, this study provides a reference for further strengthening the utilization of agricultural machinery and promoting large-scale land operations.